KONFLIK TOKOH UTAMA DALAM NOVEL RAHASIA SALINEM KARYA BRILLIAN YOTENEGA DAN WISNU SURYANING ADJI - Rahmawati, Rahmawati; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was focused on the main character’s internal conflict in a novel, titled Rahasia Salinem by Brillian Yotenega and Wisnu Suryaning Adji and used as material in learning the Indonesian language in the twelve-grade of a senior high school. The research method was a qualitative descriptive study. The approach used was the literary psychology approach. The data were collected through the documentary study technique. The researcher and data cards were the tools of data collection. The data source in this research was the novel of Rahasia Salinem by Brillian Yotenega and Wisnu Suryaning Adji, while the data were internal and external conflicts in the form of quotes, phrases, sentences or paragraphs. Based on the results of data analysis regarding internal and external conflicts, internal conflicts of the main character included; feelings of surrender, worry, doubt, anger, unhappiness, wonder, sadness, fear, and confusion. External conflicts of Salinem as the main character included social conflicts. Social conflicts experienced by Salinem included; bickering, fighting, and debating. The analysis was conducted by observing internal and external conflicts experienced by the main character based on the literacy psychology approach by using personality structure theories, namely, idea, ego, and super ego.        Keywords:  Conflict, Character, Literature Psychological.